2016
DOI: 10.1007/s12008-016-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Full scale fatigue test performed to the bolster beam of a railway vehicle

Abstract: Many structural elements are exposed to conditions of load that are difficult to consider during the design stage, such as environment uncertainties, random impacts, overloads and inherent material idealization amongst others, hence, miss-estimating its life-time cycle. One way to test those designs is to construct a representative full-scale specimen and test it under the most critical load conditions in a controlled laboratory. Herein, we present a case of study of the fatigue test performed over a bolster b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Bae et al 11 developed a new methodology of identifying fundamental fatigue load from observed data by using engineering data analytics techniques. Following the results of a finite element method (FEM) analysis previously computed for load hypothesis, Gutie´rrez-Carvajal et al 12 presented a case study of the fatigue test performed over a bolster beam of a railway vehicle. By combining PAVE test and virtual fatigue analysis technique, Sun et al 13 analyzed the fatigue life of the integrated body structure of a light commercial vehicle, and the correlation between CAE analysis and PAVE intensified durability test is validated.…”
Section: Introductionmentioning
confidence: 99%
“…Bae et al 11 developed a new methodology of identifying fundamental fatigue load from observed data by using engineering data analytics techniques. Following the results of a finite element method (FEM) analysis previously computed for load hypothesis, Gutie´rrez-Carvajal et al 12 presented a case study of the fatigue test performed over a bolster beam of a railway vehicle. By combining PAVE test and virtual fatigue analysis technique, Sun et al 13 analyzed the fatigue life of the integrated body structure of a light commercial vehicle, and the correlation between CAE analysis and PAVE intensified durability test is validated.…”
Section: Introductionmentioning
confidence: 99%
“…A special area in the field of vibration research is the transport system [1][2][3][4]. Drivers and passengers are exposed to various types of vibrations, which depending on the severity and frequency affect the comfort of the traveler and also indirectly on safety.…”
Section: Introductionmentioning
confidence: 99%
“…Wheel-rail contact is very important for safety of rail vehicle, thus it is scientific problem considered by many researchers [1,2,[6][7][8]17]. This paper presents research on rail vibration generated under the wheel-rail contact of driving rail vehicle.…”
Section: Introductionmentioning
confidence: 99%